2020
DOI: 10.1111/exd.14187
|View full text |Cite
|
Sign up to set email alerts
|

A heterozygous mutation in GJB2 (Cx26F142L) associated with deafness and recurrent skin rashes results in connexin assembly deficiencies

Abstract: Mutations in GJB2 encoding Connexin 26 (CX26) are associated with hearing loss and hyperproliferative skin disorders of differing severity including keratitis‐ichthyosis‐deafness (KID) and Vohwinkel syndrome. A 6‐year‐old Caucasian girl who presented with recurrent skin rashes and sensorineural hearing loss harboured a heterozygous point mutation in GJB2 (c.424T > C; p.F142L). To characterize the impact of CX26F142L on cellular events. Plasmids CX26WT, CX26F142L, CX26G12R (KID) or CX26D66H (Vohwinkel) were tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Dye uptake assays showed that cells expressing the N54K mutant demonstrated a highly variable incidence of PI uptake, and cells expressing the S183F mutant displayed no increase in PI uptake, indicating nonfunctional hemichannels [ 24 ]. Marziano et al [ 52 ] and Albuloushi et al [ 87 ] obtained similar results for the hemichannel activity of the D66H and F142L mutants. Both variants resulted in syndromic HL and had reduced hemichannel activity.…”
Section: Association Between Gjb2 Missense Variant...mentioning
confidence: 53%
“…Dye uptake assays showed that cells expressing the N54K mutant demonstrated a highly variable incidence of PI uptake, and cells expressing the S183F mutant displayed no increase in PI uptake, indicating nonfunctional hemichannels [ 24 ]. Marziano et al [ 52 ] and Albuloushi et al [ 87 ] obtained similar results for the hemichannel activity of the D66H and F142L mutants. Both variants resulted in syndromic HL and had reduced hemichannel activity.…”
Section: Association Between Gjb2 Missense Variant...mentioning
confidence: 53%
“…Several mutations induce lethal phenotypes and are associated with loss of cell viability [ 83 , 84 , 85 ]. Recently, we proposed a further Class 4 mutation group associated with hyperkeratosis, mucositis and deafness, where cell model studies revealed cell death and a collapse of the microtubule network, but limited connexin channel function (e.g., F142L, CX31G45E) [ 86 , 87 ].…”
Section: Connexins and The Skinmentioning
confidence: 99%
“…As such, CX26 and CX43, critical connexins in epithelial tissue are unable to form heterotypic structures [ 88 , 89 ]. Recent studies report changes in CX26 mutation oligomerization compatibility, allowing aberrant interactions with CX43 with exacerbated hemichannel activity but non-functional gap junction channels [ 78 , 86 , 90 ], with each mutation uniquely altering the 3D structure in terms of charge, pore size, hydrophobicity, etc. It is also conceivable that altered CX43:CX26 heteromeric channels influence unique metabolic exchange and influence asymmetric cell division required for the stratification of the epidermis, thereby contributing to the hyperproliferative status of the skin [ 91 ].…”
Section: Connexins and The Skinmentioning
confidence: 99%
See 1 more Smart Citation
“…This disease is usually accompanied by many other medical disorders, for example sensorineural deafness, ichthyosis, vitiligo and mental retardation, severely affecting the patients' physical and mental health 2 . However, the effective therapeutic treatment of VS is still lacking in the clinical settings 3 …”
Section: Introductionmentioning
confidence: 99%